Riwayat Sang Anoman - Eko Wahyu Prihantoro (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2023)
The History of Sang Anoman is a story that contains the whereabouts of Anoman since birth and aducated by tree Gods so that he is able to find his unity by returning to his origins and is shon in the form of adance drama with dialoge on the devolepment of wayang orang. The show is aimed at the ritual awareness of the community in oneness. What is meant by ritual awarenes is something important related to life and death, while the comumunity in oneness is togetherness of the community in preserving life, namely the three main things related land water and air. Thus the history of Sang Anoman fosters sympathy an empathy for the people to care for the universe.